Epistemic Causality in Literary Discourse of M. Amis - S. A. Petrenko; A. Ph. Petrenko (Научный диалог, 2022)
Epistemic causal relations in the discourse of Martin Amis are studied on the example of complex statements with the connector because, which expresses the non-self-causal relationship between propositions. The relevance of the study is due to the importance of studying the logical and semantic essence of causality as a basic category of human thinking. The mechanism of causal argumentation is considered from the point of view of the cognitive interaction of cause-and-effect elements of discourse.  Attention is paid to epistemic argumentative relations, which are a sequential unfolding of the thought process with the reverse / regressive conditionality of events, where the opinion-conclusion is followed by the argument from which this conclusion was formulated. A wide range of functional and semantic roles of the causal connector as an explicator of epistemic causality is described. The contextual analysis of microsituations with the connector because reveals a variety of logical connections between inversely related propositions, as well as in constructions close to paratactic ones. The specificity of the functional capabilities of the conjunction under study is described, which leads the authors to create a classification of epistemic causal relations with the causal conjunction because in English is described. Four epistemic functions of the connector because are identified: discursive-reflexive, expressive-epistemic, implicit-epistemic, and logical-discursive.